Mercury Hazards to Living Organisms - Eisler, Ronald (CRC Press, 2009)
Complex and ever changing in its forms and functions, the element mercury follows a convoluted course through the environment and up the food chain. The process is complicated further by the fact that the difference between tolerable natural background levels and harmful effects in the environment is exceptionally small and still not completely understood. Written by recognized national and international authority on chemical risk assessment, Ronald Eisler, Mercury Hazards to Living Organisms explores the biological, physical, and chemical properties of mercury and its compounds. Rich in facts and information, the book provides a fundamental look at the issues.